Youth, suicide attempts and low level of education: A Danish historical register-based cohort study of the outcome of suicide attempt. (December 2015) - Christiansen, Erik; Agerbo, Esben; Larsen, Kim Juul; Bilenberg, Niels; Stenager, Elsebeth
Background: In Denmark, it is a political goal that 95% of all young people should complete an upper secondary education. For some young people, this goal can be difficult to achieve. An association has been established between suicidal behaviour and school performance. Aim: We hypothesise that young people who have attempted suicide have a lower chance of finishing secondary education. Methods: We used Danish historical population registers to perform a longitudinal cohort design and extended Cox regression modelling to estimate crude and adjusted estimates of the effect of suicide attempt on secondary education. We used the birth cohorts 1983–1989, and all subjects were followed from birth until the end of 2011 ( n  = 355, 725). Results: For suicide attempters, the likelihood of completing secondary education was one-third of non-attempters (crude hazard ratio = 0.38). A part of the impact can be explained by confounding factors. Individuals with a suicide attempt at age 16–20 years or with multiple suicide attempts were most likely not to complete secondary education. Compared to mentally ill non-attempters, suicide attempters with mental illness were more likely not to finish secondary education. Conclusion: A suicide attempt is not necessarily causal for not finishing secondary education, but it is a marker, and it predicts an increased likelihood of not finishing secondary education. We need to identify individuals at risk for suicide attempts and subsequently provide the necessary support. Completing secondary education is important, as it provides better chances of employment, higher wages and more opportunities for individuals in the future.